2006
DOI: 10.1682/jrrd.2004.11.0143
|View full text |Cite
|
Sign up to set email alerts
|

A noncontact sensor for measurement of distal residual-limb position during walking

Abstract: Abstract-A simple noncontact device was implemented for measuring the position of the distal residual limb relative to the prosthetic socket during ambulation. The device was a small and lightweight photoelectric sensor positioned within a frame mounted immediately beneath the socket. Calibration tests showed that the sensor had a displacement range of 60.0 mm. The root-mean-square error for all sources of error considered (different reflective surfaces, peak-to-peak signal noise, drift, nonlinearity, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 14 publications
(24 reference statements)
5
56
0
Order By: Relevance
“…13,17,19,20 Based on our literature review, most of the researchers measured the displacement between the bone and the socket or the soft tissue by using different techniques in static position 2,11,[15][16][17][18]26,27 or during the gait. 14,[19][20][21][22]25 Some tried to mimic the gait by adding certain loads to the prosthesis. 13,20 However, no research was found to measure the displacement between the Iceross Dermo ® liner (thickness: 3mm) and the socket in transtibial or transfemoral prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,17,19,20 Based on our literature review, most of the researchers measured the displacement between the bone and the socket or the soft tissue by using different techniques in static position 2,11,[15][16][17][18]26,27 or during the gait. 14,[19][20][21][22]25 Some tried to mimic the gait by adding certain loads to the prosthesis. 13,20 However, no research was found to measure the displacement between the Iceross Dermo ® liner (thickness: 3mm) and the socket in transtibial or transfemoral prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the camera brings the possibility of easy and fast determination of pistoning between the liner and socket and it can be a safe method if X-ray exposure is a concern. 14,25,28 This technique can also be used for measuring the pistoning in transfemoral prostheses. In our study, we could not examine the real pistoning during the gait (dynamic), but we tried to mimic the gait by using different loads.…”
Section: Discussionmentioning
confidence: 99%
“…32 Recently, a simple photographic method has been reported 29,36-37 and finally, Gholizadeh et al 38 used Vicon motion analysis system to evaluate pistoning in transtibial amputees. The literature review revealed that the majority of researchers measured the displacement between the bone and the socket, the liner and socket or the soft tissue, by using different techniques in static position 19,29,32,[34][35][36][37][38]53,55 or during dynamic tasks 33,35,54,[60][61] to check pistoning inside the socket. Therefore, the methods available were classified according to whether they utilized static or dynamic pistoning.…”
Section: Pistoning Measurement Methodsmentioning
confidence: 99%
“…Thus, both clinicians and researchers should be able to determine the quality of suspension and prevent the negative effects of pistoning (such as gait deviation, skin breakdown, and discomfort) by pistoning measurement [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…These include X-ray [12,20,[23][24][25], spiral computerized tomography [26], and photoelectric sensors [22]. These measurement methods are mostly useful for measuring the bone movement inside the socket.…”
Section: Introductionmentioning
confidence: 99%